The Noble Widow's Place in the Patriarchal Household: The Life and Career of Jeanne de Gontault - Kalas, Robert J. (The sixteenth century journal, 1993)
Jeanne de Gontault's diverse activities as a widow allow us to better understand the economic and political roles that a noblewoman in sixteenth-century France could play, both in a private way within the context of the family, and in a more public way at court. Her experiences raise several important historiographical questions, for they demonstrate that it was possible for a noblewoman to have economic independence, her own "career," and a role in the business and economic affairs of her family. Jeanne's actions call into question the traditional image of the widow as a woman who was important within the family during her son's minority. Jeanne's influence did not disappear when Henri reached his majority. Instead, she continued to be a key figure in the Noailles clan, working with and through the men in the family to advance the economic and political interests of that family during the last quarter of the sixteenth century.